Kajian Hukum Atas Penggunaan Articial Intrlligence (AI) oleh Kantor Hukum di dalam Menangani Sebuah Perkara (International Forum of Researchers and Lecturers, 2025)
The rapid advancement of digital technology, particularly Artificial Intelligence (AI), has reshaped various sectors, including the field of law. This study aims to examine the integration of AI in law firms’ operations, focusing on its potential benefits, legal challenges, and ethical implications in the Indonesian legal context. This research employs a qualitative approach through a normative juridical method, supported by literature review and case analysis related to the use of AI in legal practice. Relevant legislation, including Law No. 11 of 2008 on Electronic Information and Transactions, is analyzed to assess the existing regulatory framework. The study reveals that while AI enhances efficiency in tasks such as document analysis, case prediction, and legal drafting, it also raises concerns about algorithm reliability, data bias, and the absence of specific AI-related legal regulations in Indonesia. Law firms must ensure transparency, accountability, and ethical responsibility when adopting AI to align with the principles of justice. Human interaction remains crucial to maintain trust and professional integrity in client services. The research contributes to the ongoing discourse on developing legal and ethical frameworks for AI implementation in the legal sector. It suggests the need for comprehensive regulation and professional guidelines to optimize AI utilization while safeguarding justice and ethical standards. The study is intended for publication in a national academic journal.